Thematic analysis a practical guide - Braun, Virginia (SAGE, 2022)
"Developed and adapted by the authors of this book, thematic analysis (TA) is one of the most popular qualitative data analytic techniques in psychology and the social and health sciences. Building on the success of Braun & Clarke's 2006 paper first outlining their approach which has over 100,000 citations on Google Scholar - this book is the definitive guide to TA and your support system throughout your TA journeys. It addresses the common questions surrounding TA as well as developments in the field, offering a highly accessible and practical discussion of doing TA situated within a clear understanding of the wider terrain of qualitative research."